Peran Brand Image dalam Memediasi Pengaruh Social Media Marketing terhadap Repeat Purchase pada Fast-Food Restaurant di Kota Medan - Muhammad Fahmi; Muhammad Arif; Salman Farisi; Nadia Ika Purnama (Universitas Samudra, 2020)
This study aims to analyze the effect of social media marketing on brand image and repeat purchases, and to analyze the role of brand image in mediating the effect of social media marketing on repeat purchases in the Fast-Food Restaurant industry in Medan. The respondents are consumers who have made purchases at five fast food restaurants in Medan. 140 people were selected using random sampling. Data collected using questionnaire and interviews, and analyzed using descriptive and path analysis. The results proved that social media marketing was significantly influenced brand image; brand image was significantly influenced repeat purchase; and, social media marketing was significantly influenced repeat purchase. Moreover, social media marketing proved has no significant effect on repeat purchase through brand image as mediator.